Assessing Adolescents' Preferences for Contemporary Drink Attributes - Akmalia Salsabila Darmawan; Ai Nurhayati; Atat Siti Nurani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The rising popularity of contemporary beverages among adolescents, despite their high sugar content and low nutritional value, has raised significant public health concerns. This study investigates the key factors influencing the consumption of contemporary beverages—such as boba milk tea, cheese tea, milk coffee, and Thai tea—among secondary school students in Bandung, Indonesia. Employing a quantitative, cross-sectional descriptive method with a sample of 110 respondents aged 15–19, data were collected via structured questionnaires and analyzed using descriptive statistics. Findings reveal that price is the most influential factor driving consumption interest (75%), followed by packaging (71%), quality (68%), and brand (68%). Adolescents prioritize affordability and functional packaging features such as portability and spill resistance, while sensory preferences (e.g., taste, temperature, and texture) and customizable options (e.g., sugar and ice levels) enhance perceived quality. Although brand recognition contributes to purchasing decisions, it is secondary to practical and economic considerations. The study underscores the need for targeted health communication strategies and product reformulation to align adolescents' beverage preferences with healthier consumption behaviors. These insights are valuable for stakeholders in the beverage industry and public health sectors aiming to balance market demands with adolescent nutrition education.